2008
DOI: 10.3748/wjg.14.651
|View full text |Cite
|
Sign up to set email alerts
|

Should we redefine large common bile duct stone?

Abstract: The definition of large stones is not clear ranging from 10 mm to 15 mm and does not include the lower common bile duct (CBD) diameter. Three hundred and four patients who underwent endoscopic retrograde cholangiopancreatography and stone extraction were retrospectively analyzed over a 1-year period. Sixteen patients were different from others in that 10 patients with large stones had stone extraction with a wire basket or a balloon catheter and 6 patients with small stones had stone extraction with mechanical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 5 publications
0
17
0
1
Order By: Relevance
“…Strictures below a stone may also affect the ability to extract these CBD stones. Some authors have suggested that any definition of a large CBD stone should include a relation to the lower CBD diameter to enable a relative comparison . Hence, we would like to propose a definition of large CBD stone as >15 mm with a stone to CBD ratio of >1.0 …”
Section: Nomenclature and Definitionmentioning
confidence: 99%
“…Strictures below a stone may also affect the ability to extract these CBD stones. Some authors have suggested that any definition of a large CBD stone should include a relation to the lower CBD diameter to enable a relative comparison . Hence, we would like to propose a definition of large CBD stone as >15 mm with a stone to CBD ratio of >1.0 …”
Section: Nomenclature and Definitionmentioning
confidence: 99%
“…Other predictors have been cited in the litt erature: a papilla localized in the bulb or in the 3rd portion CBD: common bile duct. of the duodenum [1,5], a surgical reconstruction (Billroth II or Y-branch of Roux) [1,19,24] and a cuboid or barrel form of the stones [25,26]. The predictors of failure of CBD clearance found in the literature are summarized in Table 5.…”
Section: Discussionmentioning
confidence: 99%
“…There is no consensus in the literature to define a large stone: most authors use a cut-off between 10 and 15mm [ 20 , 24 ]. Sharma et al recommend including the diameter of the CBD to define a large calculus and thus speaking of a large stone if the size of the stone is greater than the diameter of the CBD by more than 2 mm (ratio of the stone size/diameter of CBD> 1) [ 24 ]. This ratio (stone size/diameter of the CBD >1) was found as a predictor of failure in multivariate analysis [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, some biliary stones may become a challenge, depending on their location, number and especially dimensions. While there is no consensus regarding the definition of complexity criteria, difficulties may arise due to local and anatomical conditions such as strictures, diverticula, disproportion between the size of distal bile duct and the stone (difference greater than 2 mm), post – surgical altered anatomy and multiple (10 or more) or large stones (with a diameter of ≥ 15 mm) 1 8 10 11 12 13 .…”
Section: Introductionmentioning
confidence: 99%